Soleus H-Reflex Inhibition Decreases During 30 s Static Stretching of Plantar Flexors, Showing Two Recovery Steps - Budini, Francesco; Christova, Monica; Gallasch, Eugen; Rafolt, Dietmar; Tilp, Markus (Frontiers in Physiology, 2018)
During the period when the ankle joint is kept in a dorsiflexed position, the soleus H-reflex is inhibited. The nature of this inhibition is not fully understood. One hypothesis is that the decrease in spinal excitability could be attributed to post-activation depression of muscle spindle afferents due to their higher firing rate during the stretch-and-hold procedure. As the static stretching position is maintained though, a partial restoration of the neurotransmitter is expected and should mirror a decrease in H-reflex inhibition. In the present study we explored the time course of spinal excitability during a period of stretching. Soleus H-reflex was elicited during a passive dorsiflexion movement, at 3, 6, 9, 12, 18, 21 and 25 seconds during maximal ankle dorsiflexion, during plantar flexion and after stretching, in 12 healthy young individuals. Measurements during passive dorsiflexion, plantar flexion and after stretching were all performed with the ankle at 100° angle; measurements during static stretching were performed at individual maximal dorsiflexion. H-reflex was strongly inhibited during the dorsiflexion movement and at maximal dorsiflexion (p<.0001) but recovered during plantar flexion and after stretching. During stretching H-reflex showed a recovery pattern (r=.836, P=.019) with two distinct recovery steps at 6 and 21 seconds into stretching. It is hypothesised that the H-reflex inhibition observed until 18 seconds into stretching is the result of post-activation depression of Ia afferent caused by the passive dorsiflexion movement needed to move the ankle into testing position. From 21 seconds into stretching, the lower inhibition could be caused by a weaker post-activation depression, inhibition from secondary afferents or post-synaptic inhibitions.